Academic profession and university in the context of modern institutional reforms - Ismoilov Temurbek Islomovich (Research Parks Publishers, 2021)
The article reveals university education performs the function of socialization and preparation of students for life as citizens of the country, then the attention of the state to academic autonomy and freedom of education is quite natural. High school researchers Barnett and Middlehurst identify various difficulties in the academic profession that fit into the concept of functional-role conflict and are mainly related to research and teaching.